Competing Strategies Evaluation on Consumer Visit Reduction: A Case Study on a Culinary Business Operation - SULISTYADI, Budiono; WENING, Nur; HERAWAN, Tutut (Journal of Environmental Management and Tourism; Vol 10 No 2 (2019): JEMT VOlume X Issue 2(34) Spring 2019, 2019)
This research evaluates the competing strategy of a culinary business in dealing with the ever-changing business dynamics. The analysis is conducted qualitatively using Porter’s industrial structural analysis based on the five competitive powers, namely threat of new entrants, bargaining power of buyers, threat of substitute products or services, bargaining power of suppliers, and rivalry among existing competitors. The research was conducted at Tenpura Hana restaurant, which is currently experiencing a reduction in consumer visit, and other respondents, namely four competing restaurants nearby and three other restaurants that are potentially able to offer replacement products. Data of new entrants’ threat, replacement product threat, and rivalry among existing competitors are obtained by means of survey and data collection using questionnaires for Tenpura Hana Restaurant, four competing restaurants nearby and three other restaurants that are potentially able to offer replacement products. Data on buyers’ bargaining power and suppliers’ bargaining power are obtained from records at Tenpura Hana Restaurant. The analysis results show that Tenpura Hana restaurant uses the generic competing strategy of differentiation against pressures which cause a decline in customer visits. With this research, culinary business practitioners are expected to be able to evaluate their business competing strategies.